Experimental study on the effect of finishing parameters on surface roughness in magneto-rheological abrasive flow finishing process. (September 2015) - Dehghan Ghadikolaei, Amir; Vahdati, Mehrdad
In this study, a novel precision finishing process for complex internal geometries using smart magneto-rheological polishing fluid is developed. Magneto-rheological abrasive flow finishing process provides better control over rheological properties of abrasive-laden finishing medium that exhibits changes in rheological behavior in the presence of external magnetic field. The finishing fluid used in this study contains SiC and iron particles with a combination of specific volume percentage of glycerin and liquid paraffin as abrasive, magnetizable and base medium parts, respectively. The smart characteristics of magneto-rheological fluid are utilized to precisely control finishing forces to control surface quality. A hydro-mechanical device is used to provide experimental setup in order to investigate the effects of different parameters on surface roughness. This device consists of a hydro-mechanical power unit, abrasive fluid containers, permanent Nd-Fe magnets, workpiece fixtures and a base frame. Experiments were conducted on austenitic stainless steel (AISI304), aluminum (7075 alloy) and copper (unalloyed) with different magnetic field strength, abrasive particle size and finishing time cycles. It is observed that by decreasing magnetic field strength, the surface roughness decreases in all three materials. Besides, with increase in abrasive particle mesh number, surface roughness tends to be higher. However, there is a slight difference observed through different finishing cycle times. The specific applications of this process are finishing fluid guidelines in precise instruments like capillary tubes in drug delivery setups.